Chitosan Derivatives and Their Application in Biomedicine - Wenqian Wang (International Journal of Molecular Sciences, 2020)
Chitosan is a product of the deacetylation of chitin, which is widely found in nature. Chitosan is insoluble in water and most organic solvents, which seriously limits both its application scope and applicable fields. However, chitosan contains active functional groups that are liable to chemical reactions; thus, chitosan derivatives can be obtained through the chemical modification of chitosan. The modification of chitosan has been an important aspect of chitosan research, showing a better solubility, pH-sensitive targeting, an increased number of delivery systems, etc. This review summarizes the modification of chitosan by acylation, carboxylation, alkylation, and quaternization in order to improve the water solubility, pH sensitivity, and the targeting of chitosan derivatives. The applications of chitosan derivatives in the antibacterial, sustained slowly release, targeting, and delivery system fields are also described. Chitosan derivatives will have a large impact and show potential in biomedicine for the development of drugs in future.